Seven theaters in search of revenue : a study of pricing strategies in the arts sector - Rindler, Rebecca M.; Oster, Sharon M.; Nagy, Andrea R. ([London] : SAGE, 2016)
How much should tickets to Saturday night's show cost? Theatres weigh a number of concerns when deciding how to set admission prices. This study explains the complex considerations that theatres need to factor in when arriving at their admission fees.
Originally Published in: Rindler, R. M., Oster, S., & Nagy, A. R. (2008). Seven Theaters in Search of Revenue: A Study of Pricing Strategies in the Arts Sector. 08-014. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Pricing -- Case studies; Theater management -- Case studies